(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
Consensual concession is governed by the provisions of Law No. 23-17, which defines the conditions and procedures for granting economic real estate belonging to the state’s private domain to implement investment projects. Economic real estate is defined as any property belonging to the state’s private domain or acquired by the Algerian Investment Promotion Agency (AIPA) that is suitable for an investment project under the provisions of the investment law. Consensual concession is subject to specific conditions, some of which are related to the nature of the applicant seeking the concession, while others concern the property itself. It is also governed by a set of procedures that must be followed before the property can be alienated. The Algerian Investment Promotion Agency is the sole authority authorized to grant property designated for investment via a consensual concession, which can be converted into a concession for alienation. This process is initiated by an investor’s application submitted through the digital platform for investors.